Managing spot blotch disease in wheat: Conventional to molecular aspects - Roy, Chandan; Xinyao He; Gahtyari, Navin C.; Mahapatra, Sunita; Singh, Pawan K. (Frontiers Media, 2023)
Spot blotch (SB) caused by Bipolaris sorokiniana (teleomorph Cochliobolus sativus) is one of the devastating diseases of wheat in the warm and humid growing areas around the world. B. sorokiniana can infect leaves, stem, roots, rachis and seeds, and is able to produce toxins like helminthosporol and sorokinianin. No wheat variety is immune to SB; hence, an integrated disease management strategy is indispensable in disease prone areas. A range of fungicides, especially the triazole group, have shown good effects in reducing the disease, and crop-rotation, tillage and early sowing are among the favorable cultural management methods. Resistance is mostly quantitative, being governed by QTLs with minor effects, mapped on all the wheat chromosomes. Only four QTLs with major effects have been designated as Sb1 through Sb4. Despite, marker assisted breeding for SB resistance in wheat is scarce. Better understanding of wheat genome assemblies, functional genomics and cloning of resistance genes will further accelerate breeding for SB resistance in wheat.